Bambusicolous Arthrinium Species in Guangdong Province, China - Senanayake, Indunil C.; Bhat, Jayarama D.; Cheewangkoon, Ratchadawan; Xie, Ning (Frontiers in Microbiology, 2020)
A survey of bambusicolous fungi in Bijiashan Mountain Park, Shenzhen, Guangdong Province, China, revealed several arthrinium-like taxa from dead sheaths, twigs and clumps of Bambusa species. Phylogenetic relationships were investigated based on morphology and combined analyses of the ITS, LSU, β-tubulin and tef 1–α gene sequences. Based on morphological characteristics and phylogenetic data, Arthrinium acutiapicum sp. nov. and A. pseudorasikravindrae sp. nov. are introduced herein with descriptions and illustrations. Additionally, two new locality records of Arthrinium bambusae and A. guizhouense are described and illustrated.